Efektivitas Konseling Lintas Budaya Berbasis Transactional Analysis dalam Mengatasi Masalah Manajemen Keuangan pada Mahasiswa Perantauan Melayu Riau: Studi Eksperimen Kasus Tunggal - Khairul Arifin; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Migrant students often face difficulties adjusting to new social environments, particularly in managing personal finances. This study aims to examine the effectiveness of cross-cultural counseling based on the Transactional Analysis (TA) approach in addressing financial management problems among migrant students with a Melayu Riau cultural background. The method used is a Single Case Experimental Design (SCED) with an A-B design, where phase A represents the baseline condition prior to intervention and phase B represents the counseling intervention phase. The research subject is one student with the initials DD, aged 19 years, from Taluak Kuantan, Riau. Data were collected through pre-intervention assessment interviews, behavioral observation during counseling sessions, and post-intervention follow-up interviews. Behavioral analysis was conducted using the Behavioral Pattern (PTL) framework comprising Pancadaya, Likuladu, and Masidu components. Results show positive behavioral changes following the intervention: the client was able to manage finances more systematically, understood financial priorities, and maintained an active social life without compromising financial stability. These findings indicate that TA-based cross-cultural counseling is effective in enhancing self-control and financial awareness among migrant students.